Do social influences, awareness, or experience matter? Toward a better understanding of Farm-related Injury Risk Perception among agricultural science college students in Ireland - Mohammadrezaei, Mohammad; Meredith, David; McNamara, John; Kinsella, James; Flannery, Sinéad (Frontiers in Public Health, 2023)
Introduction Formal farm safety education/training should be tailored, in terms of the approach, content and delivery, to students undertaking agriculture education and training to enhance Farm-related Injury Risk Perception (FIRP). To this end, this paper assesses factor(s) explaining or predicting levels of FIRP amongst students studying for a degree in agriculture science. Methods A cross-sectional online survey was conducted with a nationally representative sample of Bachelor of Agriculture Science (BAgrSc) students (N = 417) (aged 18–20) in Ireland. Descriptive [frequency and cross-tabulations) and inferential (Ordinal Logistic Regression (OLR)] analyses were applied to evaluate the effects of social influences, experience (of farming, of a near-miss or injury), and awareness (of others who were injured or killed on the farm) on FIRP. Results The study found that social influences negatively affected FIRP (P < 0.05). A relatively small number of students reported experiencing an injury (n = 56, 13.4%) that resulted in them being unable to participate in educational or social activities. A quarter of the respondents did, however, record experiencing a near-miss/close call (n = 106, 25.4%). A notable proportion (n = 144, 34.5%) of students had personal connections to someone who died as a consequence of a farm-related incident and 56.4% (n = 235) knew someone who was moderately or severely injured. OLR findings established that experiencing a severe injury, having a near-miss or close call, and awareness of a farm-related death or injury positively affects FIRP (P < 0.05). Conclusions Perception of farm risks amongst students in Ireland is low. Students who recorded higher levels of risk perception were, however, more likely to report experiencing a near-miss, close call or severe injury, or knowing someone who experienced a farm-related injury or fatality. Farmers, family or friends were found to negatively impact the FIRP and this reflects previous research findings. Our findings highlight the need for education and training programs to enhance opportunities for student peer-to-peer learning through sharing of experiences and/or knowledge of farm injuries and/or fatalities. Such activities will enhance awareness and understanding amongst the general population of students leading to increased FIRP and contribute to a reduction in risk-taking.